The Role of Learning Media with the Integration of the Mathematics Learning Process in the Era of Society 5.0 - Adinda Permata; Yayu Nurhayati Rahayu; Dedi Mulyadi (Gunung Djati Conference Series, 2022)
The purpose of this study was to determine the relationship of mathematics learning media in the renewal of the learning process in the era of society 5.0 or the era of very rapid technological development. The method used is the Literature Study method or System Literature Review. Collecting data from data collection in the library with the existing study topics discussed in the literature study by reading, recording and processing these sources. The results of the study indicate that the relationship between learning media and learning mathematics in the era of society 5.0 has a very close relationship. The world of education that has evolved using many technology systems such as during the pandemic case, the world of learning changed completely and was assisted by using learning media such as learning videos, the use of e-learning, WhatsApp-based e-learning media, Edmodo-assisted learning media, web-based learning, including online learning media such as google classroom and video conference zoom meetings where the role of new media in the education sector in the era of society 5.0. That way the role of the teacher is also very concerned in the creativity of renewal or the integrity of teaching using media using technology